TINJAUAN IMPLEMENTASI TEORI PERENCANAAN DALAM PENYUSUNAN DOKUMEN STRATEGI SANITASI KABUPATEN BENER MERIAH - Suek, Jonathan Badawi Wempi; Arbani, Inggar Rayi; Gayo, Andhyka Putra Arie (STKIP PGRI Situbondo, 2024)
The Regency Sanitation Strategy (RSS) document represents the government's initiative to address the consequences of market failure resulting from insufficient sanitation services, that lead to environmental pollution and a decline in public health. This failure has hindered the attainment of the universal access target (100-0-100), characterized by shortcomings in environmental quality, health, and community welfare in Bener Meriah Regency. This study aims to assess the application of planning theory in formulating RSS documents in Bener Meriah Regency. The research employed methods such as document review, interviews, stakeholder mapping, and qualitative descriptive analysis of interview findings. The outcomes include identifying stakeholders, planning approaches, the role of planners, and uncovering weaknesses and ethical issues in the planning process. Conclusions drawn from the discussion are: 1) Six key actors are involved in preparing the RSS document; 2) Various approaches, including mixed scanning, comprehensive rationale, advocacy planning, and collaborative planning, are employed in the RSS preparation process in Bener Meriah; 3) All planning roles play a part in the RSS preparation process; and 4) Weaknesses in the document preparation process encompass inadequate data quality, unrealistic aspects of funding and human resources, and limited engagement of external stakeholders.